Mercury and its effect on human health: a review of the literature - Siti Thomas Zulaikhah; Joko Wahyuwibowo; Arrizki Azka Pratama (International Journal of Public Health Science (IJPHS), 2020)
Mercury in human body is a free radical that can cause depletion of glutathione (GSH) and hoarding of H2O2, leading to shorten the age of erythrocytes and cause haemolysis. Approximately 90% organic form can be absorbed by the intestinal wall, while inorganic forms are only about 10%. The initial form can also penetrate the blood and placental barrier so that it can cause teratogenic effects and nervous disorders. The effects of mercury toxicity on humans depend on the chemical form of mercury, dosage, age of people exposed, length of exposure, entry into the body, fish diet and consumption of seafood. Mercury is able to bind sulfidril proteins in cells resulting in nonspecific cell injury or even cell death, cessation of microtubule formation, enzyme inhibition, oxidative stress, cessation of protein and DNA synthesis, and autoimmune responses. Classified into a very toxic metal, mercury can trigger the formation of ROS, hydrogen peroxide, lipid peroxidation, hydroxyl radicals that can inhibit enzymes, cell damage, DNA damage, protein structure damage, disruption on the body's antioxidant metabolism, especially superoxide dismutase (SOD) and glutathione peroxidase (GPx). Mercury exposure is associated with an increased risk of hypertension, myocardial infarction, coronary dysfunction, and atherosclerosis. This review is clearly in line to investigate the effect of mercury on human health based on previous research, article and other literature sources.